TRACKING THE COMMITMENT OF LOCAL POLITICAL ELITES IN REVITALIZING PEAT AND MANGROVE ECOSYSTEMS IN RIAU'S COASTAL AREAS - Tito Handoko; Hasanuddin; Erdianto; Fadhiilatun Nisa (RADJA PUBLIKA, 2026)
This study critically analyzes the commitment of local political elites on the Riau coast in the revitalization of peat and mangrove ecosystems. With the approach of political ecology and qualitative case study methods, it was found that the commitment displayed was symbolic and instrumental. This is evident from the inconsistency between formal policies and minimal budget allocations, as well as licensing practices that support the extractive industry. Key findings suggest that elite actions are determined more by calculations of economic-political interests tied to the electoral cycle than by authentic ecological sustainability visions.